A question of heroes - Joaquin, Nick 1917-; Anvil Publishing, Inc. (Pasig City Anvil, 2005)
On Philippine heroes and their role in the Philippine revolution.
First published: Manila, Philippines: Filipinas Foundation, Inc., 1977.
In English.
Keywords: Heroes -- Philippines; Philippines -- Biography; Philippines -- History and criticism -- Biography; Philippines -- History -- Revolution, 1896-1898.